Ultra Thin Resistively Loaded FSS Absorber For Polarisation Independent Operation At Large Incident Angles - Cahill, Robert; Zabri@Suhaimi, Siti Normi; Schuchinsky, Alexander G. (2014)
In this paper we report on a resistively loaded Frequency Selective Surface (FSS) absorber design which is insensitive to the polarization of microwave signals incident at angles of 45º ± 5º. The metal backed periodic structure is composed of an array of conductive rectangular loops, each loaded with a resistor at the center of the four sides. The geometry of the absorber and the resistance value of the vertical and horizontal resistor pairs are carefully chosen so that the structure presents a real impedance of 377 Ohms at the center operating frequency for both TE and TM polarized waves incident at 45º. Numerical predictions of the electromagnetic scattering from three different absorbers, designed to work at X band, are used to investigate the effect of thickness and resistance value on the reflectivity bandwidth and angular sensitivity.